Effect of Substituted Concentration on Structure and Magnetic Properties of Y3Fe5-xInxO12 - Thi Hoai Huong, Vu; Thuy Nguyet, Dao Thi; Duong, Nguyen Phuc (VNU Journal of Science: Mathematics - Physics; Vol 34 No 4DO - 10.25073/2588-1124/vnumap.4298, 2018)
Abstract: This study examines the effect of substituted concentration on the structure and magnetic properties of Y 3 Fe 5-x In x O 12 ( x = 0.1 ÷ 0.7) powder samples prepared using the sol-gel method. The morphological properties of the samples were analysed using XRD, SEM. The single phase of garnet was obtained in x = 0.1 ÷ 0.6 samples. The lattice parameters of the samples exhibit a linear increase with the increasing In 3+ content, which can be explained by a substitution of In 3+ ions for Fe 3+ ions, considering the larger ionic radius of In 3+ compared with that of Fe 3+ . Crystallite sizes were determined via the XRD data which are of 38 – 49 nm while the particle sizes were estimated from SEM images to be in range of 50 - 100 nm. Magnetization and Curie temperature of the single phase samples were studied by magnetization curves in fields up to 10 kOe and in the temperature range from 80 K to 560K. With the increase of In 3+ , the magnetization gradually increases while the Curie temperature decreases due to the occupation of In atoms at the a sites and the reduction of intersublattice interaction, respectively. Keywords : Yttrium iron garnet, Indium substitution, cation distribution, magnetization, Curie temperature. References [1] R. L. Streever, Anisotropic exchange in ErIG, Journal of Magnetism and Magnetic Materials 278 (1-2) (2014) 223-230. [2] N.I. Tsidaeva, The magnetic and magnetooptical properties of Y-substituted erbium iron garnet single crystals, Journal of Alloys and Compounds 374 (1-2) (2004) 160-164. [3] Y.Nakata, T. Okada, M. Maeda, S. Higuchi and K. Ueda, Effect of oxidation dynamics on the film characteristics of Ce:YIG thin films deposited by pulsed laser deposition, Optics and Lasers in Engineering 44 (2) 2006, 147-154. [4] M. Laulajainen, P. Paturi, J. Raittila, H. Huhtinen, A.B. Abrahamsen, N.H. Andersen and R. Laiho, BixY3-xFe5O12 thin film prepared by laser ablation for magneto-optical imaging of superconducting thin films, Journal of Magnetism and Magnetic Materials 279 (2-3) (2004) 218-223. [5] A.A. Lagutin, G.E. Fedorov, J. Vanacken and D. Herlach, Magnetic properties of dysprosium Yttrium ferrite garnet in pulsed magnetic fields at low temperatures, Journal of Magnetism and Mmagnetic Materials 195 (1999) 97-106. [6] S.A. Nikotov, Nonlinearity: Magneto-optic microwave interactions. Towards new devices, Journal of Magnetism and Magnetic Materials (196-197) (1999) 400-403. [7] C.S. Tsai, Wideband tunable microwave devices using, European Ceramic Society 23 (14) (2003) 2721-2726. [8] A. Sztaniszlav, M. Farkas-Jahnke, M. Balla, Kinetics of garnet formation in In3+ substituted systems, Journal of Magnetism and Magnetic Materials 215-216 (2000) 188-193. [9] R.G. Vidhate, V.D. Murumkas, R.G. Dorik, N.M. Makne, S.R. Nimbore, K.M. Jadhav, Magnetic properties of In Substituted ytrium iron garnet (YIG), Rev. Res. 1(10) (2012) 1-4. [10] G. Cuijing, Z. Wei, J. Rongjin, Z. Yanwei, Effect of In3+ substitution on the structure and magnetic properties of multi-doped YIG ferrites with low saturation magnetizations, Journal of Magnetism and Magnetic Materials 323, (2011) 611-615. [11] Vu Thi Hoai Huong, Dao Thi Thuy Nguyet, To Thanh Loan, Luong Ngoc Anh, Nguyen Phuc Duong, Than Duc Hien, Structural and magnetic properties of Y3-2xCa2xFe5-xVxO12 nanoparticles prepared by sol-gel method, Proceeding of the 3rd International Conference on Advanced Materials and Nanotechnology (2016) 219-223. [12] Imaddin A. Al-Omari, Ralph Skomski, David J. Sellmyer, Magnetic properties of Y3-2xCa2xFe5-xVxO12 garnets, Advances in Materials Physics and Chemistry 2 (2012) 116-120. [13] Rodziah Nazlan, Mansorhashim, Idza Riati Ibrahim, Fadzidah Mohd Idris, Wan Norailiana Wan Ab Rahman, Nor Hapishah Abdullah, Ismayadi Ismail, Saikannu Kanagesan, Zulkifly Abbas, Rabaah Syahidah Azis, Influence of Indium substitution and microstructure changes on the magnetic properties evolution of Y3Fe5-xInxO12 (x = 0.0 – 0.4), Journal of Material Science: Materials in Electronics 26, 6 (2015) 3596-3609. [14] M. Niyaifar, A. Beitollahi, N. Shiri, M. Mozaffari, J. Amighian, Effect of indium addition on the structure and magnetic properties of YIG, Journal of Magnetism and Magnetic Materials 322 (2010) 777 – 779. [15] J. Richard Cunningham Jr and Elmer E. Anderson, Effect of indium substitution in Yttrium iron garnet. High permeability garnets, Journal of Applied Physics 32, (1961) S388. [16] L. Vegard Dr. Phil, LV. Results of crystal analysis. –III, Philosophical magazine Series 6, 32: 191, 505 – 518. [17] Ronald W. Armstrong, Crystal dislocations, Crystals 6, 1 (2016) 9. [18] Gerald F. Dionne, Molecular field coefficients of substituted yttrium iron garnets, Journal of Applied Physics. 41 (1970) 4874. [19] M.A. Gilleo, Ferromagnetic insulators: Garnets, in: E.P. Wohlfarth (Ed.), Handbook of Magnetic Materials, Volume 2, North-Holland Publishing Company, 1980, 1-54. [20] Z. Azadi Motlagh, M. Mozaffari, J. Smighian, Preparation of nano-sized Al-substituted yttrium iron garnets by the mechanochemical method and investigation of their magnetic properties, Journal of Magnetism and Magnetic Materials 321 (2009) 1980-1984. [21] P. Belov and I.S. Lyubutin, Effective magnetic fields at tin nuclei in substituted iron garnets CaxY3-x SnxFe5-x O12, Soviet Physics JETP 22 (3) (1966) 518 – 520.